2013
DOI: 10.1073/pnas.1307107110
|View full text |Cite
|
Sign up to set email alerts
|

Insulin growth factor signaling is regulated by microRNA-486, an underexpressed microRNA in lung cancer

Abstract: MicroRNAs (miRNAs) are small 19- to 24-nt noncoding RNAs that have the capacity to regulate fundamental biological processes essential for cancer initiation and progression. In cancer, miRNAs may function as oncogenes or tumor suppressors. Here, we conducted global profiling for miRNAs in a cohort of stage 1 nonsmall cell lung cancers ( n = 81) and determined that miR-486 was the most down-regulated miRNA in tumors compared with adjacent uninvolved lung tissues, suggesting that miR-486 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
121
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 33 publications
11
121
1
1
Order By: Relevance
“…But different studies reported different conclusions about miR-486's regulation in cancers. Some studies reported that miR-486 was reduced in peripheral blood or tissues (27)(28)(29) of lung cancer patients, while others reported that it was up-regulation in lung cancer patients (30) or those patients with up-regulated level miR-486 in plasma had short overall survival (31). Those inconsistent findings were controversial and different study samples selection may be an important reason for this, which needs to be further studied and comprehensively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…But different studies reported different conclusions about miR-486's regulation in cancers. Some studies reported that miR-486 was reduced in peripheral blood or tissues (27)(28)(29) of lung cancer patients, while others reported that it was up-regulation in lung cancer patients (30) or those patients with up-regulated level miR-486 in plasma had short overall survival (31). Those inconsistent findings were controversial and different study samples selection may be an important reason for this, which needs to be further studied and comprehensively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that miR-486-5p has also been found to be downregulated in numerous other cancer types, including pancreatic cancer (34), gastric cancer (29), osteosarcoma (35), and lung cancer (23), however, the mechanism of miR-486-5p downregulation in those types of cancer, including HCC, is largely unknown. According to previous studies, miR-486-5p downregulation in HCC tissues could be highly accredited to its chromosomal location (8p11.21), which is one of the most typically occurring genomic deletion regions, containing potential tumor suppressor genes (29).…”
Section: A B Discussionmentioning
confidence: 99%
“…Focusing on the gatekeeper of the IGF-axis, IGF-1R, several miRNAs, including miR-145 and miR-99a, have been found to act as tumor suppressors in HCC through direct targeting of IGF-1R (21,22). Notably, it was recently reported that miR-486-5p directly targets IGF-1R in lung cancer (23). However, this has not previously been investigated in HCC.…”
Section: Microrna-486-5p Enhances Hepatocellular Carcinoma Tumor Suppmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-486-5p may act as a tumor-suppressor, would provide potential diagnostic and therapeutic targets for the disease, contributing to the progression and metastasis of non-small cell lung cancer (NSCLC) by targeting ARHGAP5 (Wang et al, 2014). miR-486 directly targets components of insulin growth factor (IGF) signaling including insulin-like growth factor 1 (IGF1), IGF1 receptor (IGF1R), and phosphoinositide-3-kinase, regulatory subunit 1 (alpha) (PIK3R1, or p85a) and functions as a potent tumor suppressor of lung cancer both in vitro and in vivo (Peng et al, 2013). miR-499 could contribute to poor prognosis by modulating cancer-related genes' expression and thus involve tumorigenesis and anti-chemotherapy (Qiu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%